The impact of antithrombin III supplementation on prognosis during extracorporeal membrane oxygenation: a systematic review and meta-analysis - Ya-Ting Zeng; Yi-Nan Liu; Zi-Han Chen; Qiang Chen; Kai-Peng Sun (Annals of Medicine, 2025)
Objective To systematically evaluate the impact of antithrombin III (AT III) supplementation on the prognosis of patients undergoing extracorporeal membrane oxygenation (ECMO).Materials and methods A comprehensive literature search was conducted in PubMed, Web of Science, Embase, and the Cochrane Library for studies assessing the effects of AT III supplementation on ECMO patient outcomes. The risk of bias was assessed using the Cochrane Risk of Bias and The Newcastle-Ottawa Scale.Results A total of six studies involving 18,641 ECMO-treated patients were included. The meta-analysis showed that AT III supplementation did not reduce mortality in ECMO patients (RR = 1.17, 95% CI: 0.85–1.60, p = 0.34) and had no significant benefit in reducing bleeding events (RR = 1.04, 95% CI: 0.90–1.21, p = 0.56) or thrombosis (RR = 1.29, 95% CI: 0.81–2.05, p = 0.29). Subgroup analysis revealed that in cardiac ECMO patients, AT III supplementation was associated with an increased mortality but a reduced risk of thromboembolism. Conversely, in other ECMO support types, AT III supplementation was linked to a higher incidence of thromboembolism, with adult patients also showing an increased thromboembolism rate. No statistically significant differences were observed in other subgroup analyses.Conclusion Overall, AT III supplementation does not reduce in-hospital mortality, bleeding, or thrombotic complications in ECMO patients and may even pose risks in certain populations. Therefore, routine AT III supplementation in ECMO patients may be not currently recommended.